Natriuretic Peptides Regulate the Expression of Tissue Factor and PAI-1 in Endothelial Cells - Yoshizumi, Masami; Tsuji, Hajime; Nishimura, Hiromi; Masuda, Haruchika; Kunieda, Yasushi; Kawano, Hidehiko; Kimura, Shinzo; Sugano, Tatsuya; Kitamura, Hidetsugu; Nakagawa, Katsumi; Nakagawa, Masao (Thrombosis and Haemostasis, 1999)
In the present study, we demonstrate that brain natriuretic peptide (BNP) and C-type natriuretic peptide (CNP) interact with angiotensin II (Ang II) in regulative blood coagulation and fibrinolysis by suppressing the expressions of both tissue factor (TF) and plasminogen activator inhibitor-1 (PAI-1) induced by Ang II. The expressions of TF and PAI-1 mRNA were analyzed by northern blotting methods, and the activities of TF on the surface of rat aortic endothelial cells (RAECs) and PAI-1 in the culture media were respectively measured by chromogenic assay.Both BNP and CNP suppressed the expressions of TF and PAI-1 mRNA induced by Ang II in a time- and concentration-dependent manner via cGMP cascade, which suppressions were accompanied by respective decrease in activities of TF and PAI-1. However, neither the expression of tissue factor pathway inhibitor (TFPI) nor tissue-type plasminogen activator (TPA) mRNA was affected by the treatment of BNP and CNP.
Keywords: BNP; CNP; Ang II; coagulation; fibrinolysis